A review of single-phase pressure drop characteristics microchannels with bends - Endro Junianto; Jooned Hendrarsakti (National Research and Innovation Agency, 2021)
Microfluidic use in various innovative research, many fields aimed at developing an application device related to handling fluid flows in miniature scale systems. On the other hand, on the use of micro-devices for fluid flow the existence of bends cannot be avoided. This research aims to make a comprehensive study of fluid flow characteristics through a microchannel with several possible bends. This study was conducted by comparing Reynolds number versus pressure drop in a serpentine microchannel to gain bends loss coefficient. The result showed that the fluid flow with Re 100 did not affect the pressure drop, but on the Reynolds number above that, the pressure drop was increased along with the appears of vortices in the outer and inner walls around the channel bends which causes an increase in an additional pressure drop. The other finding shows that the reduction in diameter bend tube can increase the pressure drop.